Financial Statement Preparation Analysis Using Islamic Boarding School Accounting Guidelines at Al-Mukhtariyah - Sitia Hotmin Harahap; Yenni Samri Juliati Nasution; Laylan Syafina (E-Jurnal Akuntansi, 2025)
The preparation of financial reports in accordance with Islamic boarding school accounting guidelines plays a crucial role in increasing the transparency and accountability of the institution. This study aims to analyze the process of preparing financial reports at Al-Mukhtariyah Islamic Boarding School, Sungai Dua, which includes financial position reports, activity reports, cash flow reports, and notes to the financial statements. Data are analyzed through the stages of reduction, presentation, and conclusion. The results indicate that Islamic boarding schools still use simple financial reports due to limited understanding and information regarding Islamic boarding school accounting guidelines. This finding emphasizes the need to improve accounting literacy so that financial report preparation can be carried out more precisely, accurately, and in accordance with applicable standards.